2022
DOI: 10.3389/fmolb.2022.966843
|View full text |Cite
|
Sign up to set email alerts
|

A cuproptosis-related lncRNAs signature for prognosis, chemotherapy, and immune checkpoint blockade therapy of low-grade glioma

Abstract: Cuproptosis is a new type of cell death that is associated with mitochondrial respiration of the tricarboxylic acid cycle. Previous studies showed that long non-coding RNAs (lncRNAs) regulated low-grade glioma (LGG) progression. However, the potential applications of cuproptosis-related lncRNAs (CRLs) in LGG were not explored. A comprehensive analysis was performed in The Cancer Genome Atlas (TCGA) and Chinese Glioma Genome Atlas (CGGA) cohorts. We first screened two distinct cuproptosis subtypes based on prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 72 publications
2
7
0
Order By: Relevance
“… Ouyang et al (2022) presented models based on lncRNA and CRG levels; cuproptosis-associated glutaminase gene expression reflected the prognosis of glioma patients. The prognostic model of Yan et al (2022) used the levels of cuproptosis-associated lncRNAs to identify appropriate immune checkpoint blockade (ICB) therapies for LGG patients. We employed LASSO Cox’s regression analysis when constructing our prognostic model; the risk score was based on the levels of five CRGs (FDX1, DLD, LIAS, LIPT1, and PDHA1).…”
Section: Discussionmentioning
confidence: 99%
“… Ouyang et al (2022) presented models based on lncRNA and CRG levels; cuproptosis-associated glutaminase gene expression reflected the prognosis of glioma patients. The prognostic model of Yan et al (2022) used the levels of cuproptosis-associated lncRNAs to identify appropriate immune checkpoint blockade (ICB) therapies for LGG patients. We employed LASSO Cox’s regression analysis when constructing our prognostic model; the risk score was based on the levels of five CRGs (FDX1, DLD, LIAS, LIPT1, and PDHA1).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Chen et alestablished a cuproptosis activity score (CuAS) based on bulk tumor and single-cell transcriptome data, suggesting that cuproptosis mediates glioma aggressiveness and neoplasm-immune interactions ( Chen et al, 2022 ). In addition, Yan et alreported that cuproptosis-related lncRNAs can guide LGG treatment, as they could divide LGG patients into different groups according to the response to immunotherapy ( Yan et al, 2022 ). In addition, two subclusters of glioma patients were identified based on CRG expression, which was correlated with tumor driver gene mutations and the response to chemotherapy, according to Wang et al ( Wang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…This work constructed a novel prognostic model using a LASSO analysis, and it included six PRGs, namely CASP4, CASP5, CASP9, GSDMC, PLCG1, and IL18. Recent studies have shown that genes related to cuproptosis [ 32 , 33 ] and ferroptosis [ 34 , 35 ] are predictive of the prognosis of LGG patients, and corresponding prognostic models have been constructed. Compared with them, our model has good 1-, 3-, 5- year AUC values ( Supplementary Table S1 ).…”
Section: Discussionmentioning
confidence: 99%
“…The following supporting information can be downloaded at: , Figure S1: Cox proportional hazards (PH) test before constructing the nomogram; Table S1: Comparison of AUC values of different prognostic models based on TCGA-LGG data. References [ 32 , 33 , 34 , 35 ] are cited in Supplementary Materials…”
mentioning
confidence: 99%